Efficient and Selective Palladium‐Catalysed C‐3 Urea Couplings to 3, 5‐Dichloro‐2(1H)‐pyrazinones. Issue 5 (8th January 2015) - Belfrage, Anna Karin; Gising, Johan; Svensson, Fredrik; Åkerblom, Eva; Sköld, Christian; Sandström, Anja
Abstract: The development of a robust palladium‐catalysed urea N ‐arylation protocol to install various ureas at the 3‐position of the 2(1 H )‐pyrazinone scaffold is described. The method involves Pd(OAc)2 in combination with bidentate ligands, xantphos [4, 5‐bis(diphenylphosphino)‐9, 9‐dimethylxanthene] in particular, and resulted in good to excellent coupling yields of aliphatic, aromatic, and sterically hindered ureas. Furthermore, the C‐3 chlorine was shown to be selectively displaced in the presence of aryl halide ureas, and this finding was supported by density functional theory (DFT) calculations. This allows further diversification of the scaffold for the production of compound libraries. Overall, the protocol facilitates further exploitation of pyrazinones as beta‐sheet‐inducing scaffolds in the development of sophisticated peptidomimetics/protease inhibitors. This is exemplified here by the synthesis of a new pyrazinone‐based hepatitis C virus (HCV) NS3 protease inhibitor. Abstract : An efficient palladium‐catalysed urea N ‐arylation protocol to install various functionalized ureas at the 3‐position of the 2(1 H )‐pyrazinone is described. The procedure was used in the synthesis of a new inhibitor targeting the hepatitis C virus NS3 protease.